Ethics and research with children : a case-based approach - Kodish, Eric (OUP E-Books., 2005)
In this edited volume, a diverse group of scholars present and discuss challenging cases in the field of paediatric research ethics. After years of debate and controversy, fundamental questions about the morality of paediatric research persist: is it ever permissible to use a child as a means to an end? How much authority should parents have over decisions about research that involves young children? What should be the role of the older child in decisions about research participation? How do the dynamics of hope and desperation influence decisions about research involving dying children? Should children or their parents be paid for participation in research? What about economic incentives for doctors, researchers and the pharmaceutical industry? Most importantly, how can the twin goals of access to the benefits of clinical research and protection from research risk be reconciled? Following an introductory overview by editor Eric David Kodish, the book is divided into three sections of case studies: Research Involving Healthy Children, Research Involving At Risk Children, and Research Involving Children with Serious Illness.; Each case raises compelling ethical issues, and the analysis presented in each chapter illuminate the challenges posed across a wide spectrum of both research protocols and stories of individual case-based approach, this book provides a balanced and through account of the enduring dilemmas that arise when children become research subjects.